Incidence of Neonatal Phenylketonuria in Hormozgan Province, Southern Iran, 2014-2016 - Farzaneh Dehghan (Journal of Global Pharma Technology, 2018)
Background and Aim: Phenylketonuria is a hereditary, autosomal recessive disease characterized by deficiency of hepatic phenylalanine hydroxylase. Dietary PKU treatment and regular monitoring of blood Phe are responsible to prevent symptoms. Therefore, present research was performed with the objective of determining incidence of PKU in the Hormozgan Province, South of Iran. Material and Method: This cross sectional study was carried out in Bandar Abbas, Hormozgan among 71677 neonates, who were born from March 21, 2014 to March 21, 2016. The newborns were screened during the days 3 to 5 after birth. Finally, the incidence rate was calculated and statistical analysis conducted by Statistical Package for Social Sciences (SPSS) version 22 (SPSS Inc, Chicago, IL, USA). Results: Among study population, 36705 (51.2%) of cases were male and 34972 (49.8%) were female and 15 cases (12 in first year and 3 in second year) were ELISA positive (considered as suspected PKA) and referred for confirmatory HPLC test. Finally, three neonates were confirmed as PKA positive cases by HPLC test. Overall incidence rate of neonatal PKA in two studied years was 1:23866. Conclusion: We can conclude that the incidence rate of phenylketonuria in southern Iran is reduced to 1:16987 in 2015 and 1:37736 in 2016, which is probably due to improved knowledge of general population of Iran about controllable determinants of PKU.Keywords: Phenylketonuria, Newborn, Incidence, Iran.